Parameter Genetik dan Seleksi Sorgum [Sorghum bicolor (L.) Moench] Populasi F4 Hasil Single Seed Descent (SSD) - Sulistyowati, Yuli; koesoemaningtyas, Tri; Sopandie, Didy; Ardie, Sintho Wahyuning; Nugroho, Satya (Perhimpunan Biologi Indonesia, 2016)
The objective of this study were to obtain information about genetic parameters of agronomic characters of sorghum populations derived from Single Seed Descent (SSD) method, and to estimate selection differensial and also to select of F4 population that have a high yield and medium plant height . The experiment was carried out at Leuwikopo Farm, Darmaga, Bogor from January to April 2014. The genetic material were F4 population derived from SSD. The results showed that based on the skewness and kurtosis values, all of the agronomy characters observed in this study were poligenic controlled and influenced by additive gene action. The genetic coefficient of variability values for all parameters varied from intermediate to high in F4 population. Agronomic characters in F4 responded positively to selection because of high broad sense heritability estimates. Correlation analysis showed that plant height, number of leaves, stem diameter, panicle length, panicle weight and 100 seed weight have significant and positive correlation to grain yield/plant. Differential value with selection intensity 10 % based on grain yield/plant will increase grain yield/plant 83.89 % and plant height 8.91 % in the next generation, whereas differensial value based on grain yield/plant and plant height will increase grain yield/plants 68.33 % and plant height 0.26 % in the next generation. It means that selected plant were expected increasing yield 83.89 % or 68.33 % in next generation.Keywords: heritability, cefficient genetic variability, correlation analysis, selection differential